New Perspectives on the Use of Cannabis in the Treatment of Psychiatric Disorders - Maria Scherma; Paolo Masia; Matteo Deidda; Walter Fratta; Gianluigi Tanda; Paola Fadda (Medicines, 2018)
Following the discovery of the endocannabinoid system and its potential as a therapeutic target for various pathological conditions, growing interest led researchers to investigate the role of cannabis and its derivatives for medical purposes. The compounds Δ9-tetrahydrocannabinol and cannabidiol are the most abundant phytocannabinoids found in cannabis extracts, as well as the most studied. The present review aims to provide an overview of the current evidence for their beneficial effects in treating psychiatric disorders, including schizophrenia, anxiety, and depression. Nevertheless, further investigations are required to clarify many pending issues, especially those relative to the assessment of benefits and risks when using cannabis for therapeutic purposes, thereby also helping national and federal jurisdictions to remain updated.